An experimental analysis of a timber Howe truss. (May 2017) - Islam, AKM Anwarul; Phillips, Daniel
Abstract: An experimental analysis was conducted on a wood Howe truss, frequently used in covered timber bridges, to determine forces in counter webs. For appropriate design and rehabilitation of a timber Howe truss bridge, it is necessary to understand the transfer of forces through the truss members, particularly through the counter webs. It is often difficult to properly model and determine forces in the counter webs using structural analysis software. In order to determine forces in counter webs, experimental load tests using strain gages and moving loads were performed on a 1/8th scale physical model of a wood Howe truss. Test results indicate that the counter webs carry a small percentage of the applied loads, which is contrary to our current consideration that counter webs are zero-force members.